Analisis Tingkat Kepuasan Pengunjung Tentang Kualitas Fasilitas Di Taman Margasatwa Dan Budaya Kinantan Kota Bukittinggi - Harahap, Fiqri Alidani; Fasandra, Fernando (Institut Seni Indonesia Padangpanjang, 2025)
The purpose of this research is to determine the level of visitor satisfaction regarding the quality of facilities at the Kinantan Wildlife Park and Cultural Park in Bukittinggi City, measured through three indicators: alignment with expectations, interest in returning visits, and willingness to recommend. This type of research is descriptive and quantitative with the population consisting of visitors to TMSBK Bukittinggi City, and the sample size of the study is 269 respondents, who filled out questionnaires distributed via Google Forms. Based on the research results and descriptive data analysis of the three indicators, the results are as follows: the alignment with expectations indicator received positive results and falls into.the good category with an average score of 3,77, the interest in returning visits indicator received positive results and also falls into the good category with an average score of 3.79, and the willingness to recommend indicator received positive results and falls into the good category with an average score of 3.90. Based on measurements across the three indicators, the conclusion drawn from this study is positive, as reflected by the average score falling within the 'Good' category according to the Likert scale intervals.